Protocatechualdehyde Rescues Oxygen-Glucose Deprivation/Reoxygenation-Induced Endothelial Cells Injury by Inducing Autophagy and Inhibiting Apoptosis via Regulation of SIRT1 - Cao, Shidong; Chen, Senmiao; Qiao, Xilin; Guo, Yan; Liu, Fang; Ding, Zhishan; Jin, Bo (Frontiers in Pharmacology, 2022)
Background: Oxidative stress induced endothelial cell death, such as apoptosis and autophagy, plays a critical role in ischemia-reperfusion injury. Protocatechualdehyde (PCA) is a major bioactive component of the traditional Chinese medicine Salvia miltiorrhiza Bunge (Lamiaceae), and it has been proved to be effective in the prevention and treatment of ischemic cardiovascular and cerebrovascular diseases. However, its role in oxidative stress-induced endothelial cell death and its underlying mechanisms remains unclear. This study aims to investigate the effects and mechanisms of PCA on endothelial cell apoptosis and autophagy induced by oxygen–glucose deprivation/reoxygenation (OGD/R) injury. Methods: After OGD/R induction, human umbilical vein endothelial cells (HUVECs) were treated with different concentrations of PCA. Cell viability, apoptosis, and autophagy were detected by Cell Counting Kit-8 assay, flow cytometry, and monodansylcadaverine assay, respectively. Western blot was applied to explore the effects of PCA on the expression levels of relevant protein factors. Results: The results show that PCA significantly promoted cell survival rate and cell proliferation and enhanced the antioxidant activity in OGD/R-induced HUVECs. PCA inhibited HUVECs apoptosis, as evidenced by decreased expression of cleaved-caspase-3, BCL2-Associated X (BAX), and increased expression of Bcl-2. PCA induced autophagy by reducing the expression of P62 while increasing the expression of Beclin-1 and LC3 II/I. Meanwhile, PCA enhanced the expression of Sirtuin 1 (SIRT1) and suppressed the expression of P53. When SIRT1 was inhibited by selisistat or SIRT1 small-interfering RNA, the anti-apoptotic and pro-autophagy abilities of PCA were attenuated. Conclusions: These results demonstrated that PCA rescued HUVECs from OGD/R-induced injury by promoting autophagy and inhibiting apoptosis through SIRT1 and could be developed as a potential therapeutic agent against ischemic diseases.